Advances in the development of histone lysine demethylase inhibitors. (August 2015) - Maes, Tamara; Carceller, Elena; Salas, Jordi; Ortega, Alberto; Buesa, Carlos
Highlights: The first wave of potent specific KDM1A inhibitors is currently in Phase I testing. The first potent specific KDM5 inhibitor is in preclinical regulatory development. There is an unsatisfied need for bona fide chemical probes for Jumonji KDMs. Dual inhibitors have the potential to synergize on KDM mechanisms. Abstract : The covalent modification of histones is closely associated with regulation of gene transcription. Chromatin modifications have been suggested to represent an epigenetic code that is dynamically 'written' and 'erased' by specialized proteins, and 'read', or interpreted, by proteins that translate the code into gene expression changes. Initially thought to be an irreversible process, histone methylation is now known to be reversed by demethylases, FAD dependent amineoxidases and by iron(II)-alpha-ketoglutarate dependent deoxygenases of the Jumonji family. Altered histone demethylase activities have been associated with human disease, including cancer. The first wave of novel investigational drugs directed against KDM1A has recently entered the clinic, and the first specific inhibitor targeting a Jumonji KDM is advancing in preclinical regulatory studies.